The Changing Role of Women in the Rural Economy - O'Leary, Jeanne M.; Economics, Statistics, and Cooperatives Service (USDA), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
Labor force participation of nonmetropolitan women rose in the 1970's but not in a consistent pattern. Their labor force participation rose 4.5% between 1973 and 1978, when they comprised 41% of the total nonmetropolitan labor force. Although women accounted for 89% of nonmetropolitan employment growth in the 1960's and 58% in the 1970's, their mean earnings declined. A greater percentage than before of nonmetropolitan women entered professional, technical, managerial, clerical, craft, and service sector occupations while fewer entered operative occupations, a former source of great employment gain for the nonmetropolitan female population. Educational level correlated positively with occupational choice and both factors together had implications for job stability. The three main factors which influenced the decisions of rural women to enter the work force are: economic considerations (resulting from inflation); changing family structure and social attitudes (the largest net increase in nonmetropolitan female labor force participation rates occurred for ages 25-34, prime childbearing years); and more job opportunities (resulting from the decentralization of manufacturing to rural areas). (SB)
ERIC Note: Paper presented at the Annual Meeting of the Rural Sociological Society (Burlington, VT, August 23-26, 1979).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attitude Change; Economic Development; Economic Factors; Employed Women; Employment Opportunities; Family Structure; Industrialization; Inflation (Economics); Labor Economics; Labor Force; Rural Areas; Rural Economics; Sex Role; Rural Women; Reports, Research; Speeches/Meeting Papers